Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Peserta Didik Pada Materi Getaran Gelombang Dan Bunyi Di Mts Salafiyah Syafi’iyah - Nova Elysia Ntobuo; Muhammad Yusuf; Suparmin Fathan; Siti Fatima; Asnianti A. Awila; Andini Pratiwi M. Mahmud; Moh. Rivaldi Bulilingo; Moh. Fadli D. Lahalik (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of guided inquiry learning model on student learning outcomes on Vibration, Wave, and Sound materials. This study was motivated by the low active involvement of students due to the dominance of giving assignments without being accompanied by explorative activities, experiments, or meaningful discussions. This condition has an impact on the achievement of less than optimal learning outcomes, especially on material that is abstract and difficult to visualise directly. Thisistudy used a quantitative approach with a quasi-experimentalipretest-posttest control group design. The research subjects consisted of two randomly selected VIII classes at MTs Salafiyah Syafi'iyah, namely the experimental class that applied the guided inquiry model and the controliclass that used direct learning. The instruments used were essay tests for pretest and posttest and observation sheets. The analysis results showedithat the average posttest of the experimental class was 81.31 and the control class was 65.15. The n-gain value of the experimental class was 0.74 (highicategory), while the control class was 0.53 (medium category). The t-test shows tcount> ttable, so Ha is accepted. Thus, the guidediinquiry model is proven effective iniimproving student learning outcomes on the material..